VO2 response in supramaximal cycling time trial exercise of 750 to 4000 m - Hettinga, F. J.; de Koning, J. J.; Foster, C. (Medicine & Science in Sports & Exercise, 2009)
Purpose: Limited research has been done on the VO2 response to time trial exercise in the supramaximal domain or during free range exercise typical of competition. The present study was designed to measure and to model the VO2 response during supramaximal time trial exercise.